PENDAMPINGAN PENENTUAN BREAK EVEN POINT (BEP) PADA UMKM ARENKULA NUSANTARA DI RANGKASBITUNG KAB. LEBAK - Amara Austin; Susana Dewi; Paniran; Sri Intan Purnama; Firmansyah (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2021)
A break event, often referred to as break even or break even, is a company situation where the total amount of income is usually the same as the total cost, or a company situation where the profit and loss is zero, the company does not make a profit but also does not suffer a loss. The aim of this assistance is to apply accounting knowledge, especially in managing funds at ArenKula Nusantara MSMEs and to assist Palm Sugar MSME managers in managing profits. This type of research is qualitative research where this method is carried out by collecting data and describing it thoroughly according to the problem being researched, so that a result will be obtained from data management which is called research results. The data used is primary data and secondary data. Based on the research results, it was concluded that fund management carried out in Micro, Small and Medium Enterprises (MSMEs) was carried out in a non-transparent manner because fund management was only carried out by the management and assistance of MSMEs. Apart from that, Aren’s business shows that the Break Even Point calculation is at a volume of 1,500 units with an income of IDR 30,000,000. This calculation is a guideline for our group in producing products by paying attention to the minimum unit limit.